A NEW APPROACH TO DETERMINE OPTIMUM INSULATION THICKNESS FOR ALL BUILDINGS IN TURKEY BASED ON HEATING LOADS AND HEAT GAINS - Ozkan, Derya B.; Onan, Cenk (AMER SOC MECHANICAL ENGINEERS, 2010)
In Turkey, Thermal Insulation Requirements for Buildings was implemented to provide energy saving in buildings in 2000. After this, more then seven hundred thousand new buildings are constructed. Determining the correct material and optimum insulation thickness are very important issues in these buildings for thermal insulation. Calculations using monthly outdoor temperatures and solar radiation are done for XPS insulation material and 4 different climatic regions in Turkey. Natural gas, the most preferred in our country is selected as fuel. P(1)-P(2) method is used to obtain enemy saving and payback period. New correlations are specified to determine optimum insulation thickness depending on building heat gains and areas. Furthermore, buildings are categorized into three building class according to external wall area and floor/roof area. Effect of change in building external wall area, floor or roof area, window area to payback period, energy saving and optimum thickness are investigated. As a result, effect of architectural design is determined on thermal insulation. All calculation results are shown in a table for four different climatic regions and three different types of buildings which have the same gross volume.
Keywords: Heating energy requirement; Buildings; P(1)-P(2) method; Insulation; Payback period; EXTERNAL WALLS; RESPECT; REGIONS; COST; Energy & Fuels; Engineering